Individual Labour Disputes - Raluca DIMITRIU (CECCAR Business Review, 2023)

(untitled)
This article presents settlement methods of labour disputes, a few basic procedural issues being also set out. Thus, the goals of the material are the understanding of individual labour disputes’ amicable settlement methods and their conciliation procedure, the identification of the court that is materially and territorially competent to have jurisdiction in labour disputes and getting familiar with the main issues regarding the settlement procedure of this type of disputes.